2016
DOI: 10.1057/crr.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Image and Reputation as Drivers of Customer Loyalty

Abstract: Prior research suggests that corporate image and reputation can contribute to relationship marketing and customer loyalty. However, little empirical evidence support the influence of these constructs on customer loyalty. This study investigates the influence of corporate image-comprised of functional and emotional aspectsand reputation on customer loyalty. A structural equation model is developed to test the research hypotheses. The study was tested using data collected from a sample of Spanish consumers in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 57 publications
10
41
1
4
Order By: Relevance
“…Similarly, we found that the business image is a factor that encourages the reputation level in restaurants; that is, the actions that it conducts for the full satisfaction of the consumer have a direct impact on the business reputation. These results are also aligned with what is stated by the main theoretical currents and by the main scholars on the topic of marketing and quality in the service (de Leaniz & del Bosque Rodríguez, 2016;Dowling, 2000;Fracarolli Nunes & Lee Park, 2017;Gray & Balmer, 1998). However, our third finding reveals that the quality of service perceived by consumers of franchise-type restaurants does not exert a significant effect on business reputation; therefore, we do not find empirical support for this relationship.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly, we found that the business image is a factor that encourages the reputation level in restaurants; that is, the actions that it conducts for the full satisfaction of the consumer have a direct impact on the business reputation. These results are also aligned with what is stated by the main theoretical currents and by the main scholars on the topic of marketing and quality in the service (de Leaniz & del Bosque Rodríguez, 2016;Dowling, 2000;Fracarolli Nunes & Lee Park, 2017;Gray & Balmer, 1998). However, our third finding reveals that the quality of service perceived by consumers of franchise-type restaurants does not exert a significant effect on business reputation; therefore, we do not find empirical support for this relationship.…”
Section: Discussionsupporting
confidence: 85%
“…The success is based on creative and innovative business models (comfortable facilities, adoption of technologies, and commitment of employees) that guarantee the basic requirements of the consumer (Ahn & Seo, 2018;. These actions have led restaurant companies to increase their sales, improve customer satisfaction, increase customer loyalty, rapidly position and actively participate in improving their reputation (de Leaniz & del Bosque Rodríguez, 2016;Namin, 2017;Yaman, 2018). These organizational and financial results are originated by the correct management of the quality of the service and that consequently are reflected in the increase of the image and reputation of the businesses dedicated to the service of restaurants (Sanchez-Franco, Cepeda-Carrion, & Roldán, 2019).…”
Section: Quality In Service In the Image And Reputation Of The Companymentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the components of corporate image evolve over time, its measurement has included functional and emotional dimensions, related to types and access to the offered services, human resource, security of transactions, trust, corporate social responsibility and other factors (de Leaniz & Rodríguez, 2016;Hussain et al, 2014;Souiden et al, 2006).…”
Section: Antecedents Of Corporate Imagementioning
confidence: 99%
“…Corporate reputation, as a social identity, is extensively used in an organization's positioning strategy because of its important influence on the consumer's choice of products and services (Brown, 1995;Bonaiuto et al, 2012;Ruiz et al, 2016;Worcester, 2009). Moreover, corporate reputation helps to attract potential investors and qualified employees (Dutton et al, 1994;Fombrun and Shanley, 1990) and contributes to develop and maintain customer loyalty (Chang, 2013;De Leaniz et al, 2016;Robertson, 1993). Ultimately, corporate reputation has a significant impact on an organization's competiveness in the market place (Barnett et al, 2000;McMillan and Joshi, 1997) as well as its financial performance (Lee and Roh, 2012;Roberts and Dowling, 2002).…”
Section: Introductionmentioning
confidence: 99%